Internal Transcribed Spacer and 16S Amplicon Sequencing Identifies Microbial Species Associated with Asbestos in New Zealand - Doyle E; Blanchon D; Wells S; de Lange P; Lockhart P; Waipara N; Manefield M; Wallis S; Berry T-A (MDPI (Basel, Switzerland), 2023)
Inhalation of asbestos fibres can cause lung inflammation and the later development of asbestosis, lung cancer, and mesothelioma, and the use of asbestos is banned in many countries. In most countries, large amounts of asbestos exists within building stock, buried in landfills, and in contaminated soil. Mechanical, thermal, and chemical treatment options do exist, but these are expensive, and they are not effective for contaminated soil, where only small numbers of asbestos fibres may be present in a large volume of soil. Research has been underway for the last 20 years into the potential use of microbial action to remove iron and other metal cations from the surface of asbestos fibres to reduce their toxicity. To access sufficient iron for metabolism, many bacteria and fungi produce organic acids, or iron-chelating siderophores, and in a growing number of experiments these have been found to degrade asbestos fibres in vitro. This paper uses the internal transcribed spacer (ITS) and 16S amplicon sequencing to investigate the fungal and bacterial diversity found on naturally-occurring asbestos minerals, asbestos-containing building materials, and asbestos-contaminated soils with a view to later selectively culturing promising species, screening them for siderophore production, and testing them with asbestos fibres in vitro. After filtering, 895 ITS and 1265 16S amplicon sequencing variants (ASVs) were detected across the 38 samples, corresponding to a range of fungal, bacteria, cyanobacterial, and lichenized fungal species. Samples from Auckland (North Island, New Zealand) asbestos cement, Auckland asbestos-contaminated soils, and raw asbestos rocks from Kahurangi National Park (South Island, New Zealand) were comprised of very different microbial communities. Five of the fungal species detected in this study are known to produce siderophores.
Keywords: New Zealand; amplicon sequencing; asbestos; bacteria; bioremediation; chrysotile; fungi; siderophores; Siderophores; New Zealand; Asbestos; Iron; Bacteria; Soil